FRI0677 IMPACT OF COMORBIDITY ON THE USE OF BIOLOGICAL AND TARGETED THERAPY IN RHEUMATIC DISEASES IN THE CLINICAL PRACTICE. (June 2019) - Karateev, Dmitry; Hamhoeva, Hava; Luchihina, Helen; Tangieva, Aminat
Abstract : Background: Comorbid conditions often accompany rheumatic diseases and can influence the prescription of immunosuppressive therapy. Comorbidity seems to be a factor that is still underestimated in actual practice. Objectives: To study the influence of comorbidity on the prescription of biological and targeted therapies in patients with rheumatic diseases (RD) in clinical practice. Methods: We perform a retrospective analysis of comorbidity and prescription of biological and targeted immunosuppressors in a group of in-patients with systemic autoimmune RD in rheumatology department. From January 2018 to January 2019, 218 patients with inflammatory RD hospitalized - 146 (67, 5%) women, mean age 50.6±14, 6 years. Diagnoses: rheumatoid arthritis - 83 patients, spondyloarthritides – 80, systemic lupus erythematosus – 19, systemic scleroderma - 16, ANCA-associated vasculitides – 10, other conditions – 10 patients. Biologics were used in 117 (53, 7%) of patients (anti-TNFs – 64 patients, rituximab – 18, tocilizumab – 16, abatacept – 8, secukinumab – 4, ustekinumab – 4, tofacitinib – 3 patients). We examined patients for comorbidities through careful examination of the history, medical records, and general therapeutic laboratory and instrumental screening. The Charlson comorbidity index calculated for every patient. Results: 174 (79.8%) patients had at least 1 comorbid condition. The most frequent comorbidities were type2 diabetes (19, 5% patients), chronic kidney disease (12, 6%), cerebrovascular accidental (11, 5%), ischemic heart disease and chronic heart failure (11%), chronic liver disease (7, 5%). Mean Charlson index was 2, 16±2, 05 in total group; it was significantly lower in patients who were treated with biological and targeted therapy (1, 64±1, 8) than in patients who did not received this therapy (2, 76±2, 1), p<0, 01. Biologics were prescribed in 81, 8% of patients without comorbidities, in comparison with 55, 3% of patients with Charlson comorbidity index 1 or 2, and 36, 3% of patients with Charlson index 3 or more. Conclusion: Comorbidity has a direct impact on the use of biological and targeted therapy in patients with rheumatic diseases in real clinical practice, limiting the ability to control the activity of the disease. It is necessary to develop a general therapeutic strategy for treating comorbid conditions in patients with rheumatic diseases. References: [1] Charlson ME, Pompei P, Ales KL, MacKenzie CR. A new method of classifying prognostic comorbidity in longitudinal studies: Development and validation. Journal of Chronic Diseases. 1987; 40 (5): 373–83 Disclosure of Interests: Dmitry Karateev Speakers bureau: Pfizer, Novartis, Janssen, Abbvie, Biocad, MSD, BMS, Hava Hamhoeva: None declared, Helen Luchihina Speakers bureau: Pfizer, Abbvie, Biocad, Aminat Tangieva: None declared